Sistem Informasi Skema Pelaporan Alokasi Dana Desa Pada Nagari - Dona Kurnia; Ryan Amanda; Murni Hayati (Politeknik Negeri Padang, 2022)
Village funds in the nagari are budgeted by the central government which are distributed to all corners of the village/nagari in Indonesia, the funds are used for activities that support the progress of the village/nagari. The information system for reporting village fund allocation schemes at the nagari is designed to assist the nagari office in the process of reporting the realization of village funds in the form of a special application with the best security system so that the realization of village funds is presented more quickly, precisely and efficiently. In this study, the author uses research methods through observation and interview data collection methods as well as system development methods, namely the Development Life Cycle System (SDLC) and a tool for designing an information system. designed. The village fund allocation reporting scheme information system in Nagari Ladang Laweh is designed to be implemented in a programming language, where the programming language used is Visual Basic 2010 with MySQL DBMS. After the research was carried out, a more structured information system was produced and was very helpful for the Ladang Laweh village office in facilitating the making of village fund allocation reports that were able to process village fund allocation reports quickly, precisely and efficiently so as to produce accurate reports and facilitate the mayor in the decision-making process. for the next budget submission.